Long-term in vivo CT tracking of mesenchymal stem cells labeled with Au@BSA@PLL nanotracers. Issue 43 (29th October 2019) - Ning, Xinyu; Bao, Hongying; Liu, Xiaoyun; Fu, Han; Wang, Weizhi; Huang, Jie; Zhang, Zhijun
Abstract : Au@BSA@PLL nanotracers were developed for long-term CT tracking of hMSCs in the treatment of pulmonary fibrosis injury. Abstract : Human mesenchymal stem cells (hMSCs) transplantation has attracted considerable interest for the treatment of pulmonary injury. Noninvasive and long-term tracking of hMSCs after transplantation in vivo, which is important for our understanding of the stem cell therapy, still remains a big challenge. Herein, we report on the development of a novel gold nanoparticle-based nanotracer to track by CT imaging the transplantation of hMSCs in vivo . Gold nanoparticles (AuNPs) were synthesized on bovine serum albumin (BSA) via an in situ growth method and modified with a poly-l -lysine (PLL) layer, yielding Au@BSA@PLL nanotracers with enhanced biocompatibility and intracellular uptake. Au@BSA@PLL nanotracers were explored for in vitro and in vivo tracking of hMSCs with computer tomography (CT). Our results showed that the endocytosis of Au@BSA@PLL by hMSCs was as high as ∼293 pg per cell. Meanwhile, the nanotracers had a negligible influence on the viability, proliferation, and osteogenic and adipogenic differentiation of the labeled hMSCs. Using a pulmonary fibrosis injury mouse model induced by bleomycin, the labeled hMSCs could be tracked by CT imaging up to 23 d after transplanted in vivo, suggesting the feasibility of Au@BSA@PLL as a potential cellular nanotracer for noninvasive and long-term CT tracking of hMSCs in lung tissue repair.